2014
DOI: 10.1088/0953-8984/26/15/156001
|View full text |Cite
|
Sign up to set email alerts
|

Parimagnetism in HoCo2and TmCo2

Abstract: X-ray magnetic circular dichroism (XMCD), longitudinal (χac) and transverse (TS) ac magnetic susceptibility have been measured in the RCo2 series (R = Ho, and Tm) as a function of temperature and applied magnetic field. We show that parimagnetism is a general behavior among the RCo2 ferrimagnetic series (R being a heavy rare-earth ion). XMCD results supply evidence of the presence of two compensation temperatures above Tc, defining two different parimagnetic configurations, which is a fully unexpected result. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 77 publications
2
12
0
Order By: Relevance
“…We suppose that these discrepancies come from dierent quality of the measured samples. Based on the characterization of our sample by XRD and EDX, we trust in a good quality of our sample showing better purity in comparison with our samples from the RCo 2 family, showing more consistent results with literature [2,6,7]. The position of anomaly denoted by T f is in the agreement with the position of ipping temperature published in [7] obtained from the XMCD measurement.…”
Section: Discussionsupporting
confidence: 86%
“…We suppose that these discrepancies come from dierent quality of the measured samples. Based on the characterization of our sample by XRD and EDX, we trust in a good quality of our sample showing better purity in comparison with our samples from the RCo 2 family, showing more consistent results with literature [2,6,7]. The position of anomaly denoted by T f is in the agreement with the position of ipping temperature published in [7] obtained from the XMCD measurement.…”
Section: Discussionsupporting
confidence: 86%
“…21,23 Two clearly defined peaks were observed in ac susceptibility, w ac (T), of HoCo 2 at T C and at T SR , and two additional minor anomalies (at B40 K and near T SR ) are present as well. 24 Bonilla et al 25 observed two major anomalies at T C and T SR plus a weak anomaly in the paramagnetic region at 126 K. Apparently, the w ac (T) data are sample dependent even though the singlephase composition of HoCo 2 alloys is claimed in nearly all published studies.…”
Section: Considering Its Neighbours In the Periodic Table (Fe And Ni)mentioning
confidence: 98%
“…It follows that the single-crystal doesn't exhibit the first order phase transition, which is crucial for the existence of the magnetic Co-sublattice. This contradiction may be clarified by the discrepancies appearing in the literature [6,[11][12][13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…In this reference the critical molecular field is related to the metamagnetic transition in the analogue YCo 2 . This fact leads to discrepancies in the literature, where one can find results with a magnetic [6,[15][16][17] as well as non-magnetic cobalt sublattice [11-14, 18, 19]. These two cases are ascribed to the observation of a FOMPT [20] or SOMPT (second order magnetic phase transition) respectively.…”
Section: Introductionmentioning
confidence: 99%